Potret Diri dan Kinerja Guru Pendidikan Agama Kristen Berdasarkan 1:Petrus 2:9-25 Terhadap Minat Belajar Siswa - Frans Simamora; Thomson Siallagan; Muryani Surbakti; John Parthotan Simamora (Sekolah Tinggi Teologi Baptis Medan, 2022)
AbstractStudents' interest in studying Christian religious education will have an impact on good learning outcomes. But in reality at this time not all students achieve interest in learning. This can be seen from the low participation of students in the learning process, both face-to-face and independent study. PAK teachers as educators must have quality standards of integrity which include responsibility, authority, independence, and discipline and professional competence to produce good performance. This is called teacher profile and performance. However, in practice, currently some PAK teachers do not have a good profile and performance. So that it leads to low student interest in learning. The purpose of this study was to determine how the profile and performance of PAK teachers based on the letter 1 Petrus 2:11-25 with student interest in learning at State Elementary Schools in Medan District, Denai Regency. The types of research used in this research are: Quantitative research with survey method. According to Singarimbun,